THE EFFORT OF LAW ENFORCEMENT IN COMBATING CORRUPTION IN SOUTH SUMATERA - Sri Suatmiati (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Crime is social phenomena that happen in every time and place, the increasing levels of crime occur due to lack of  facilities and infrastructure to cope with the development or increased crime  or that could hinder the development of crime, at the  same age of the human being as the abundance of  criminal news coverage about the corruption committed by State officials.. The Attorney is the only institution of the Government of the country has a duty and authority in the field of prosecution in law enforcement and justice in the general  judicial environment.  In carrying out its duties, the Public Prosecutor bestows the case to the Court for the examination in order to prove that a person is guilty or not for the criminal offence that indicted. The Public Prosecutor's authority as a law enforcement element in proving the criminal acts that have been committed by the defendant that is should be assign the evidence as a complete proof material  that probably related to the inference where has been a criminal offence. Similarly, what the Prosecutor did against to the law, it cannot be denied that the law itself is not sterile, pure and clean from any kind of interpretation when it implemented. The Prosecutor's role  in these conditions is urgently needed mainly  in law enforcement corruption in Indonesia. Related to the issue of social assistance that occurred in South Sumatra Prosecutor's role is extremely urgent because The State’s loss which dates to achieve Rp. 2,38 Billion,1 That's why the researcher interested to discuss it in a study because of the state and local financial managements that caused state losses so Prosecutor as well as the state prosecutor's investigation should carry out its duties in corruption. The efforts to resolve the corruption based on Presidential Instruction No.10 of 2016 on the Prevention and Combating of Corruption Action 2016 and 2017 were published on 22 September 2016 contains 31 actions to be implemented by the Ministry / Agency and Local Government, in cooperation with the Corruption Eradication Commission (KPK) and the Presidential staff Office (KSP). There for the Politics, Law, Defense Deputy and Bappenas 'Security held a socialization about the substances such this Instruction There are three objectives of this Instruction: (i) to safeguard the government's priority programs; (Ii) to strengthen and focus the yearly action that has been implemented since 2011 to 2015, to ensure relevance and emphasis of action for achieving the outcome; and (iii) to improve the performance of the core business of the K / L which is in line with the President's priorities. The Action contained in the Instruction consists of 31 actions which also includes seven sectors.  In this activity, will be sharpening relevant measure of success of the action undertaken, so that its activities can be more easily and detail during the implementation of monitoring and evaluation quarterly. Anti-Corruption Strategy indicators can be said to be successful if the public service runs transparently and effectively.  With the legal issues about How the implementation of Attorney of the Republic of Indonesia policy in implementing the social grants corruption case investigation in South Sumatra? And What is the obstacles of law enforcement in the investigation by the Prosecutor of the social grants corruption case in South Sumatera? Specifically against the corruption case, the General Attorney has issued Circular Letter about the Control of Handling of Corruption Case (SE-001 / A / JA / 01/2010) which limits the authority between the General Attorney, High Attorney and the State Attorney in handling criminal case corruption based on the amount of state laws. The provision indicates the boundaries of authority between the General Attorney, the High Attorney and the State Attorney in handling corruption cases. It is not in accordance with the provisions of Law No. 16 of 2004 relating to the scope of the prosecutor's authority, where the Attorney General's jurisdiction covers the territory of the Republic of Indonesia, The High Attorney covers include the provinces and the State Attorney covers an area of the district / city. But the handling of corruption cases has not run effectively and efficiently because there are many inactive corruption cases handled by the Prosecutor during this time. Although there is Presidential Instruction No.10 of 2016 on the Prevention and Combating of Corruption Action 2016 and 2017 were published on 22 September 2016 but  it felt that the efforts of law enforcement officers in combating corruption is still not in accordance with the Instruction. Moreover, there are still many people who feel that the Instruction will have no effect on the work of the Ministry / Agency / Commission itself in the prevention and repression of acts of corruption in Indonesia. Generally the obstacles that arise in solving the corruption includes three principal constraints, namely:1. The limited number of human resources at the Investigator, Attorney Investigator and Public Prosecutor.2.\The limited of financial resources / budget of the case handling in the activities of investigation, and prosecution. 3the limited of facilities / infrastructure that supports and promotes activities of investigation, and prosecution.